Developing Countries in the WTO - Michalopoulos, Constantine (Palgrave Macmillan UK, 2001)
Globalization means that today, more than ever before, growth in developing countries and the reduction of poverty depend on world trade and a well functioning trading system. This volume reviews developing countries trade policies and institutions, and the challenges they face in the World Trade Organization - where the rules that govern the international trading system are set
Keywords: Public policy; International relations; International economics; Development economics